THE EFFECT OF SOY TEMPEH FLOUR EXTRACT TO UTERINE HISTOLOGY OF OVARIECTOMIZED MICE - Eva Tyas Utami; Mahriani Mahriani; Nidaul Hikmah (UNEJ e-Proceeding, 2016)
Uterine is one of organs that affected by estrogen hormone. This hormone can influence to increase uterus cells proliferation. Decreasing ovum production cause decreasing of estrogen level. This situation is faced of menopause that affect on uterine development. Phytoestrogens can bind to estrogen receptor and produce estrogenic affects like endogeneous estrogen. Tempeh is known as soybean fermented and consists of high level of isoflavon as phytoestrogens. Phytoestrogens have structure like mammalian estrogen 17β-estradiol. The aim of this study was to know effects of tempeh soy fluor extracts on mice uterine strain swiss webster ovariectomized.. Dosages that used on this study are 0.21g/mL, 0.42 g/mL and 0.63g/mL. The dosages are treated by gavage during 10 and 20 days after ovariectomy.The result showed that tempeh soy fluor extracts can increase the average of uterine mass, endometrial and myometrium thickness during treatment on 10 and 20 days. The 0,63g/mL dosage increase the highest of uterine mass (0.043g), endometrium thickness (389.46μm) and myometrium thickness ( 71.30μm.).